Implications of Appointing Acting Regional Heads (Pj) for Democracy in Indonesia from the Perspective of Maslahah Mursalah - Mamnun, M. Khairu; Augusta Triputra, Adhitiya (Universitas Islam Negeri Ar-Raniry, 2025)
2024 will be a political year in Indonesia. There will be general elections and local elections that year. Not only is it seen as a democratic party, but behind that many problems have arisen, such as the term of office of the definitive regional head ends in 2022, this causes a power vacuum and will be filled by elected officials from the central government who are referred to as temporary. The direct election has the potential to be violated. The approach of research in this research are statute approach and conceptual approach. This research is descriptive-analytic. The data collection technique used in this study is a qualitative data analysis technique. This research uses the theory of democracy and maslahah mursalah. The result of the research shows that the acting regional heads have implications for the quality of democracy in Indonesia, because in practice the acting regional heads are not democratic, where there is no community participation in the recruitment process and a lack of the legitimacy of acting regional heads because they only have legal legitimacy. Then in Maslahah Murslah's view, acting regional heads have benefits and harms, but the harms are bigger.